PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL SEMPURNA LUBUKLINGGAU - Rudi Azhar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Rudi Azhar. 2020. The influence of educational background and work placement on employee performance in the Hotel Perfect Lubuklinggau. Thesis. Faculty of economics and bisiness.majoringin management (S1), University Bina Insan Lubuklinggau.In carrying out hotel business activities, we need reliable human resources that have knolledge in the hotel sector. In carrying out hotel business activities, it is necessary to have reliable human resources, namely HR who have knowledge in the field of hospitallty. This study aims to determine the effect of educational background and work placement on employee performance at the Perfect Hotel in Lubuklinggau. Human Resources is an important asset for a company, therefore HR must be managed propertly in order to contribute to the company optimally. A well –managed HR will improve the performence of the employee, which in the turn will improve the performence of the employee, which will utlimately improve overall company performence. The purpose of this research is to know and analyze the influence of educational background (X1), Work placement (X2), and on employee performence (Y). Then the multiple killer equation is obtained as follows : Y = 8.029 + 0.156 X1+ 0.965X, so the constant value of employee performence (Y) without any influence remains in the value of 8.029. Every increase of one unit of educationbal background value will increase employeee performance by 0.156 one unit. Every invrease of one increase in work placement will increase performance by 0.965 one unit. The population in thethis study were all employees of the Hotel Lubuklinggau Perfect, amounting to 15 people.The sampling technigue in the study is to use total sampling. The Result of this study indicate that partially educational background has no effect on employee performence, work placement has a significant effect on employee performence in the Hotel Perfect Lubuklinggau. Simultaneouslly educational background and work placement significantly influence employee performence variables at the Perfect Lubuklinggau Hotel.